STONE AGE HISTORIOGRAPHY OF FERGANA VALLEY - Turdikhojhayeva , Mahliyo (PT. Antis International Publisher, 2024)
The historiography of Stone Age archaeology, particularly in the context of the Ferghana Valley, remains underexplored despite its rich archaeological potential. Specific Background: This study critically examines the contributions of Ferghana archaeologists, providing a comparative analysis of their research methodologies and findings. Knowledge Gap: Existing literature lacks a comprehensive synthesis of modern archaeological excavations and their implications for understanding the Mesolithic settlements in this region. Aims: The primary aim of this article is to illuminate the archaeological significance of Stone Age monuments in the Ferghana Valley and to contextualize recent discoveries within the broader framework of Mesolithic studies. Results: The findings reveal a substantial concentration of Mesolithic sites in the Ferghana Valley, underscoring the area's importance for understanding human habitation and cultural development during this period. Novelty: This article presents new insights into the spatial organization and settlement patterns of Mesolithic communities, which have been inadequately addressed in previous research. Implications: The implications of this study extend to enhancing our understanding of early human societies in Central Asia and contribute to the global discourse on Stone Age archaeology, highlighting the need for continued research in underrepresented regions.